Analysis of the Effectiveness of the Family Hope Program in Poverty Alleviation: An Islamic Economic Perspective: Case Study - Sikumbang, Sahnila; Imsar, Imsar (Borong Newinera Publisher, 2025)
This study examines the effectiveness of the Family Hope Program (PKH) in alleviating poverty‎ from the perspective of Islamic economics, focusing on the case study of Sorkam Barat Sub-district,‎ Tapanuli Tengah Regency. The research delves into the context where despite the implementation of‎ PKH, poverty persists in the region, possibly due to misalignment with Islamic economic principles or‎ inefficiencies in the program's execution. The study poses questions regarding the PKH's impact on‎ poverty alleviation and its compatibility with Islamic economic principles. Employing a qualitative‎ approach, data collection involves interviews, document analysis, and observations. The findings‎ reveal various challenges hindering the PKH's effectiveness, such as improper targeting, lack of‎ awareness among beneficiaries, and delays in aid disbursement. In addressing these issues, the study‎ recommends enhancing the program's alignment with Islamic economic principles, improving‎ targeting mechanisms, raising awareness among beneficiaries, and streamlining aid distribution‎ processes. Ultimately, the research contributes to the discourse on poverty alleviation strategies and‎ highlights the importance of considering Islamic economic perspectives in social welfare programs.